Thermal elevation on midriff skin surface as a potential diagnostic feature for Abdominal Aortic Aneurysm using Infrared Thermography (IRT) - Ng, Eddie Yin Kwee (2022)
In this study, coupled Computational Fluid Dynamics (CFD) and Computational Heat Transfer (CHT) unsteady simulation was employed to study pulsatile blood flow through the infrarenal aorta and the subsequent bioheat transfer effects on the temperature profile on the midriff skin surface. It was observed that a thermal elevated feature was present on the midriff abdomen surface for the Abdominal Aortic Aneurysm (AAA) case while the temperature contours for the healthy aorta model were uniform. The temperature values of the thermal elevation differ from its immediate surroundings by 0.04K. An experiment was also conducted to validate the CFD simulation results, and it showed similar thermal elevation trend at the surface of the phantom. These findings are helpful to correlate the presence of an AAA to the thermal features on the midriff skin surface qualitatively and pave the way to potentially render Infrared Thermography a viable AAA diagnostic tool.